2012
DOI: 10.1155/2012/629652
|View full text |Cite
|
Sign up to set email alerts
|

Sun-Protection Habits of Primary Students in a Coastal Area of Greece

Abstract: Aim. The aim of the present study was to record habits and attitudes of primary school students in Greece regarding sun-protection measures. Materials and Methods. 2,163 students with an average age of 9.9 (±1.1) years, studying in 14 schools of a Greek region, constituted our sample. The SPSS 17.0 software was used for the statistical analysis and significance level was set to P ≤ 0.05. Results. Our sample had an equal gender distribution. 16% of the students belonged to the high-risk group, 70.2% of the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 36 publications
1
21
1
1
Order By: Relevance
“…Our findings are in agreement with those of other studies that have reported high knowledge scores regarding sun protection measures [15][16][17][18][19][20]. Also, although before the intervention the students' knowledge about sun protection factors was low (25%), after the intervention it increased to 55%, since the programme was specifically aiming at enhancing knowledge about SPF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in agreement with those of other studies that have reported high knowledge scores regarding sun protection measures [15][16][17][18][19][20]. Also, although before the intervention the students' knowledge about sun protection factors was low (25%), after the intervention it increased to 55%, since the programme was specifically aiming at enhancing knowledge about SPF.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, this was an encouraging sign for the present study. This finding could be attributed to the fact that new and healthier behavioral patterns cannot be adopted by children just on account of more knowledge, since family, peer and school influence play an important role in adopting wiser behaviors, as other studies have also shown [15,18,25].…”
Section: Discussionmentioning
confidence: 95%
“…Several other studies have also found higher percentages of adolescents using sunscreen and having a sunburn too (Linabery and Ross, 2008;Al-Naggar et al, 2011;Duignan et al, 2014). Their behavior as far as the acquirement of a tan is following the trends of young people for the acceptable beauty standards, as promoted by the Media, their peers and society, and this has been observed in other countries too (Savona et al, 2005;Saridi et al, 2012;Gefeller et al, 2014;Kyle et al, 2014).…”
Section: Discussionmentioning
confidence: 82%
“…The data included in this study were about the comparison of data of two similar studies that had taken place in the same area, in different time periods, and those data were discussed according to the knowledge and attitudes of pupils (9-18 years old) on sun protection (Saridi et al, 2012;Saridi et al, 2014a;2014c). The compared data focused on incidence of sun burn in all age groups, and recorded all these factors which intensify or prevent this incidence.…”
Section: Discussionmentioning
confidence: 99%
“…A study of male and female adolescent athletes' self-reported reasons for not protecting themselves from the sun indicated lack of perceived long-term risk, beliefs that skin cancer was easily treated, and desire for a fashionable tan (Paul, Tzelepis, Parfitt, & Girgis, 2008). Another recent study by Saridi, Bourdaki, and Rekleiti (2014) sought to explore young adolescent high school students' perceptions regarding sun-related skin cancer risk, sun protection measures including sunscreen use, and resulting sunburn incidence. No significant correlation was found between perceptions of skin cancer risk or sun protective measures and sunburn incidence.…”
Section: Review Of Literaturementioning
confidence: 99%